2019
DOI: 10.1016/j.physletb.2019.134927
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two exponentiations in N=8 supergravity

Abstract: High-energy massless gravitational scattering in N = 8 supergravity was recently analyzed at leading level in the deflection angle, uncovering an interesting connection between exponentiation of infrared divergences in momentum space and the eikonal exponentiation in impact parameter space. Here we extend that analysis to the first non trivial sub-leading level in the deflection angle which, for massless external particles, implies going to two loops, i.e. to third post-Minkowskian (3PM) order. As in the case … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 107 publications
3
54
0
Order By: Relevance
“…In ref. [51], we showed that this equation reproduces the leading terms at two-and three-loop order by using the full results for these amplitudes obtained in refs. [52,55].…”
Section: Jhep03(2020)173mentioning
confidence: 66%
See 3 more Smart Citations
“…In ref. [51], we showed that this equation reproduces the leading terms at two-and three-loop order by using the full results for these amplitudes obtained in refs. [52,55].…”
Section: Jhep03(2020)173mentioning
confidence: 66%
“…In section 2 we discuss the two types of exponentiations and the distinction between classical and quantum contributions at arbitrary loop order. In section 3 we summarize, for completeness, the check presented in [51] that the scattering data up to three loops are consistent with the leading eikonal exponentiation. In section 4 we extend the procedure to subleading terms at high energy and then concentrate on the first subleading correction.…”
Section: Jhep03(2020)173mentioning
confidence: 78%
See 2 more Smart Citations
“…There is a current debate about the recently computed 3PM O(G 3 ) contribution [21,22] which yields a divergent G 3 contribution, O(α 3 ln(γ) → ∞ as γ → ∞, while the computation of Ref. [66] (see also [30]) got a finite O(α 3 ) correction in the massless limit. [The massless limit m 1 , m 2 → 0 corresponds to γ = −(P 1 · P 2 )/(m 1 m 2 ) → ∞.]…”
Section: Tidal Contribution To the Scattering Angle And To Periasmentioning
confidence: 99%